2011
DOI: 10.4155/bio.11.214
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of A New Concept for Automated Dried Blood Spot Analysis Using Flow-Through Desorption and Online SPE–MS/MS

Abstract: Results demonstrate feasibility of the DBS SPE-MS/MS concept for efficient automation of the entire DBS analysis workflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…However, this is equally true for direct elution, where online SPE, and 2D chromatography can also be utilised (109,103) . All these processes add considerable complexity, and the aim of this study was to investigate quick and simple methods of DBS analysis that are compatible with high throughput bioanalysis, which is often a critical factor in pharmaceutical discovery and development and other screening applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is equally true for direct elution, where online SPE, and 2D chromatography can also be utilised (109,103) . All these processes add considerable complexity, and the aim of this study was to investigate quick and simple methods of DBS analysis that are compatible with high throughput bioanalysis, which is often a critical factor in pharmaceutical discovery and development and other screening applications.…”
Section: Discussionmentioning
confidence: 99%
“…Heinig et al, and Ganz et al have both reported reliable automation performance and the ability to generate quantitative validation data within guideline acceptance criteria (101,102) . The DBS SPE-MS/MS from Spark Holland has been in development for a number of years and was first formally reported on in the literature in 2011 (103) . The concept is the same as that used in the SCAP system, the DBS sample is clamped from both sides and solvent is allowed to flow through to desorb the analyte.…”
Section: On-line Dbsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced risk of infection, due the fact that pathogens are deactivated upon drying [28], further contributes to the convenient and cost-effective transport and storage. From an analytical point of view, compounds can often be extracted from DBS cards using straightforward procedures, making this technique particularly suitable for automated processing [29][30][31].…”
Section: Dried Blood Spotsmentioning
confidence: 99%
“…It was demonstrated that a significant improvement of drug recoveries could be obtained by application of heated flow-through desorption. Elevated recovery rates were observed even when a hematocrit range between 0.25 and 0.65 L/L were used [10,11].…”
mentioning
confidence: 95%